Answer:
See solution below.
Step-by-step explanation:
Answer:
x = 12
y = 13
Step-by-step explanation:
Let's assume the two numbers as x and y.
The sum of the two numbers is 25
So,
The product of the two numbers is 156
- xy = 156
- x(25 - x) = 156
- 25x - x² = 156
- x² - 25x + 156 = 0
- x² - 13x - 12x - 156 = 0
- (x - 12) • (x - 13) = 0
- x - 13 = 0
- x = 13
- x - 12 = 0
- x = 12
Hence, the two numbers are 13 and 12.
-5 is the answer ...............
Step-by-step explanation:
(given)
Let us consider :
= ![t_{1} + 1](https://tex.z-dn.net/?f=t_%7B1%7D%20%2B%201)
= ![t_{2}](https://tex.z-dn.net/?f=t_%7B2%7D)
=
=
=
Now, by substituting the above considerations in the above equation, we get:
where,
1
then it follows
n = 20
r = 4
then no. of solutions for the eqn = ![_{r}^{n + r}\textrm{C}](https://tex.z-dn.net/?f=_%7Br%7D%5E%7Bn%20%2B%20r%7D%5Ctextrm%7BC%7D)
= ![_{4}^{24}\textrm{C}](https://tex.z-dn.net/?f=_%7B4%7D%5E%7B24%7D%5Ctextrm%7BC%7D)
= 10626
Answer :
no. of solutions for the eqn 10626
Answer:
it would be 17
Step-by-step explanation: